1987
DOI: 10.1111/j.1365-2125.1987.tb03228.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of famotidine and cimetidine on the pharmacokinetics of theophylline in normal volunteers.

Abstract: The comparative effect of famotidine or cimetidine on theophylline disposition was determined in healthy volunteers. Cimetidine, but not famotidine, caused a reduction in the rate of elimination of theophylline. The mean total body clearance of theophylline was reduced from 57.6 ml min-1 before cimetidine to 39.5 ml min'-during cimetidine; and the half-life was prolonged from 8.7 h before cimetidine to 12 h during cimetidine. The volume of distribution and renal excretion of theophylline were not affected by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…While apixaban is metabolized primarily by CYP3A4 and is a substrate for P-glycoprotein and breast cancer resistance protein, famotidine is minimally metabolized, is primarily eliminated unchanged in urine, and is a substrate for P-glycoprotein 20. Famotidine has minimal potential for CYP450-mediated drug–drug interactions 2224. However, it is an inhibitor of hOCT uptake transporters 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While apixaban is metabolized primarily by CYP3A4 and is a substrate for P-glycoprotein and breast cancer resistance protein, famotidine is minimally metabolized, is primarily eliminated unchanged in urine, and is a substrate for P-glycoprotein 20. Famotidine has minimal potential for CYP450-mediated drug–drug interactions 2224. However, it is an inhibitor of hOCT uptake transporters 25.…”
Section: Discussionmentioning
confidence: 99%
“…Famotidine is minimally metabolized and primarily eliminated unchanged in the urine 21. Famotidine has minimal potential for CYP-mediated drug–drug interactions 2224…”
Section: Introductionmentioning
confidence: 99%
“…This effect is marked for orally administered cimetidine, but not when the drug is given intravenously)221] Nizatidine, ranitidine and roxatidine do not change the pharmacokinetics of theophylline (table III). Investigators have reported differing results for famotidine, from concomitant famotidine reducing the clearance of theophylline [228] to it having no effect on clearance) 192,239) Propranolol is the only ~-adrenoreceptor antagonist that reduces the clearance of theophylline (30 to 52%), [170,214] Atenolol, metoprolol and nadolol do not appear to influence its elimination (table IV).…”
Section: Enzyme Inhibitionmentioning
confidence: 92%
“…Most of the studies ascribed the amelioration of airway hyper-responsiveness to the anti-reflux effect of H2R antagonists on gastroesophageal tract, although some studies mentioned that the blockade of weak H2R signaling in airway tissue may also work in part. However, we noticed that several reports emphasized the influence of H2R antagonists on the disposition of theophylline in both healthy volunteers [31] and patients with airway disorders [32]. Although these results were thought to be related to CYP450-mediated metabolism, it could also be explained as impact on the xenobiotic transporter, such as EMT.…”
Section: Resultsmentioning
confidence: 96%